Exosomes Secreted by Microglia During Virus Infection in the Central Nervous System Activate an Inflammatory Response in Bystander Cells - Luong, Nhungoc; Olson, Julie K. (Frontiers in Cell and Developmental Biology, 2021)
Microglia become persistently infected during Theiler’s murine encephalomyelitis virus (TMEV) infection in the central nervous system (CNS) of susceptible mice. We have previously shown that microglia infected with TMEV become activated through the innate immune receptors to express type I interferons, cytokines, and chemokines. Persistent TMEV infection in the CNS promotes chronic neuroinflammation and development of demyelinating disease similar to multiple sclerosis. In the current studies, we wanted to determine whether TMEV - infected microglia secrete exosomes which contribute to neuroinflammation in the CNS thus promoting the development of demyelinating disease. Exosomes are vesicles containing RNA, DNA, and proteins that are released from one cell and taken up by another cell to facilitate communication between cells. These studies isolated exosomes secreted by microglia during TMEV infection in vitro as well as exosomes secreted by microglia during early TMEV infection in mice. These studies show that microglia secrete exosomes during TMEV infection which contain the viral RNA coding region. The exosomes secreted by microglia during TMEV infection can be taken up by uninfected bystander cells, including CNS resident microglia, astrocytes, and neurons. The viral RNA in the exosomes can be transferred to the bystander cells. In addition, the bystander cells that took up these exosomes were activated through the innate immune response to express type I interferons, IFN-alpha and IFN-beta, pro-inflammatory cytokines, IL-6, IL-12, and TNF-alpha, and chemokines, CCL2. Most interestingly, exosomes secreted by microglia during early TMEV infection in mice activated an inflammatory response when transferred to the brains of naïve mice. These results show that exosomes secreted by microglia during early TMEV infection contain viral RNA and can activate uninfected bystander CNS cells to promote an inflammatory immune response. Thus, exosomes secreted by microglia during virus infection may promote viral persistence and neuroinflammation which contributes to the development of demyelinating disease.